2015
DOI: 10.1016/j.dnarep.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between ALKBH2 DNA repair enzyme and PCNA is direct, mediated by the hydrophobic pocket of PCNA and perturbed in naturally-occurring ALKBH2 variants

Abstract: Human AlkB homolog 2 (ALKBH2) is a DNA repair enzyme that catalyzes the direct reversal of DNA methylation damage through oxidative demethylation. While ALKBH2 colocalizes with proliferating cell nuclear antigen (PCNA) in DNA replication foci, it remains unknown whether these two proteins alone form a complex or require additional components for interaction. Here, we demonstrate that ALKBH2 can directly interact with PCNA independent from other cellular factors, and we identify the hydrophobic pocket of PCNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
(35 reference statements)
0
22
0
Order By: Relevance
“…We also examined the way ZRANB3 interacts with PCNA by solving structures of PCNA:ZRANB3(PIP) and PCNA:ZRANB3(APIM) complexes. We found that, despite dissimilarities between the PIP box and the APIM motif consensus sequences, both motifs occupy the same binding site on the PCNA surface30 and share the basic topology with a characteristic 3 10 helix. However, our data also point to the differences between the two motifs, and reveal specific interaction networks by which they form stable PCNA complexes.…”
Section: Discussionmentioning
confidence: 87%
“…We also examined the way ZRANB3 interacts with PCNA by solving structures of PCNA:ZRANB3(PIP) and PCNA:ZRANB3(APIM) complexes. We found that, despite dissimilarities between the PIP box and the APIM motif consensus sequences, both motifs occupy the same binding site on the PCNA surface30 and share the basic topology with a characteristic 3 10 helix. However, our data also point to the differences between the two motifs, and reveal specific interaction networks by which they form stable PCNA complexes.…”
Section: Discussionmentioning
confidence: 87%
“…More recently, in addition to the PIP box, the human AlkB homolog 2 (ALKBH2)‐PCNA‐interacting motif (APIM) is described as a PCNA‐interacting motif found in numerous proteins that are required for coordination of DNA replication and repair . A common binding site on PCNA for APIM and PIP box containing proteins has been identified strongly suggesting that these two classes of PIPs compete for the same site . The human ALKBH2 directly interacts with PCNA through a hydrophobic pocket formed by the interdomain connecting loop and internal region of PCNA.…”
Section: Pcna Is An Ancestral Protein Essential For Dna Replicationmentioning
confidence: 99%
“…38 A common binding site on PCNA for APIM and PIP box containing proteins has been identified strongly suggesting that these two classes of PIPs compete for the same site. 39 The human ALKBH2 directly interacts with PCNA through a hydrophobic pocket formed by the interdomain connecting loop and internal region of PCNA. Based on the alignment of the different ABH2s, APIM is defined as (KR)-(FYW)-(LIVA)-(LIVA)-(KR).…”
Section: Key Interacting Motifs For Pcna-protein Interactionsmentioning
confidence: 99%
“…The protein prefers substrates on double‐stranded DNA (dsDNA) . ALKBH2 interacts with other proteins like proliferating cell nuclear antigen (PCNA), involved in replication and DNA repair or DNA repair protein ATP‐dependent DNA helicase 2 subunit KU70 . Additionally, ALKBH2 shows an important role in maintaining the rDNA gene integrity and transcription .…”
Section: Impact Of Alkbh Proteins On Biological Processes In Higher Ementioning
confidence: 99%